Neural networks tricks of the trade - Montavon, Gregoire; Orr, Genevieve; Muller, Klaus-Robert (Lecture notes in computer science, 2012)
The second edition of the book adds more tricks, arising from fourteen years of work by some of the world's most prominent researchers. These can substantially improve speed, ease of implementation and accuracy when putting algorithms to work on real problems